2007
DOI: 10.1159/000103916
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis E Virus Antibodies in Patients with Chronic Hepatitis B and Chronic Hepatitis C

Abstract: Objectives: To investigate the prevalence of hepatitis E virus (HEV) among patients with chronic hepatitis B and chronic hepatitis C, serum samples were collected between January and December 2004 from patients with chronic hepatitis B and chronic hepatitis C. Methods: There were 190 adult patients with chronic hepatitis B virus (HBV) and 174 with chronic hepatitis C virus (HCV) infection in the study group. As the control group, a cohort of 178 age- and sex-matched individuals without known liver disease was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 58 publications
4
24
4
Order By: Relevance
“…[36] However, studies could not establish a strong link between these two viral infections and HEV infection in CHD patients although some evidence supports such connection. [25] We also could not demonstrate a considerable correlation between the rate of HBV infection and seropositivity for HEV in the studied patients.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…[36] However, studies could not establish a strong link between these two viral infections and HEV infection in CHD patients although some evidence supports such connection. [25] We also could not demonstrate a considerable correlation between the rate of HBV infection and seropositivity for HEV in the studied patients.…”
Section: Discussioncontrasting
confidence: 65%
“…[1316171921] The HEV seroprevalence rates reported for different countries and CHD patients have been highly variable, ranged as low as 0.9% in France, 2.6% in Italy, and as high as 7.3% or more among adult population in Spain or in Brazil. [2225] Higher prevalence of anti-HEV antibodies (IgG or IgM) than normal population was found in HD patients from Greece (9.7% vs 0.23%), Japan (9.4% vs 3.7%) or Taiwan (31% vs 8.9%). [2629] Therefore, high variations in the results have delayed a comprehensive conclusion for the existence of parenteral HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, anti-HEV IgG was detected in Japan significantly in some 23.6% (21/89) of hepatitis B and in 7.9% (12/152) of hepatitis C patients [22]. Various studies have shown that in chronic HCV infection patients, the prevalence rate of HEV infection is higher, too [52,53,54]. An association between the presence of HEV antibody and serological evidence of previous HBV or HCV infections has also been demonstrated [46].…”
Section: Hev Risk Factorsmentioning
confidence: 99%
“…Previously investigators have reported the presence of infection by hepatitis viruses in different regions of Iran, but, there aren't enough data about HCV co-infection with HEV in Iran. Previous studies have shown relatively high anti-HEV sero-prevalence in patients with HCV infection: for example Bayram reported 54% (12) and Ludi Koning reported 37%(13) IgG-HEV positive and Zaki reported 52% (14). The current study showed prevalence of IgG-HEV in HCV infected patients about 9.4%.…”
Section: Discussionmentioning
confidence: 99%